The Effect Of Phubbing In Group Learning - Mayra Musdalifah; Zaitun Qamariah (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
The purpose of this study is to look at the effect of phubbing in group learning. Phubbing, the behavior of ignoring those around them while using electronic devices, has become increasingly popular in today's digital world. The goal of group learning can be achieved by group members working together in the learning process. The quality of social interaction between group members and the success of learning can be negatively affected by the presence of phubbing in group learning environments. The library research technique used in this research literature review to collect and examine data related to the influence of phubbing in group learning. The findings of this study are expected to provide an overview of how phubbing affects the efficiency of group learning and provide a basis for reducing the adverse impact of phubbing on group learning.